Beyond client criminalization: Analyzing collaborative governance arrangements for combatting prostitution and trafficking in Sweden. Issue 3 (6th June 2019) - Erikson, Josefina; Larsson, Oscar L.
Abstract: Sweden is well known as the first country in the world to adopt client criminalization in an effort to control and eventually eliminate prostitution. Less attention has been paid to the emergence of extensive collaborative governance arrangements that serve as complements to the legal framework. The aim of this article is to provide new knowledge as it investigates the multifaceted ways in which governance arrangements have developed in Sweden, employing collaborative governance theories and the Regulatory–Intermediaries–Target model for this purpose. The strategies of responsibilization directed toward target groups that have been utilized to implement policies to control prostitution and trafficking are also explored. The article analyzes not only the rationale behind the adoption of collaborative governance in Sweden, but also the complex governance practices that have emerged in this regard, in which a range of actors are involved in policymaking and application as well as regulation. We conclude that the previous understanding of the Swedish model needs to be revised, and that although collaborative governance has made a fruitful contribution to the field in question, it also introduces new types of problems, particularly a significant increase in informality and decisionmaking outside the legal framework, primarily by civil society actors.